Modification of RSF1010-Based Broad-Host-Range Plasmids for Improved Conjugation and Cyanobacterial Bioprospecting - Bishé, Bryan (iScience, 2019)
To facilitate the genetic engineering of diverse cyanobacterial strains, we have modified broad-host-range RSF1010-based plasmids to improve transmissibility, increase copy number, and facilitate cloning. RSF1010-based plasmids replicate in diverse bacterial strains but produce low amounts of useable DNA for cloning. We previously engineered a mobAY25F mutation in RSF1010-based plasmids that improved cloning but decreased conjugation efficiency. Here, we engineered RSF1010-based plasmids to restore conjugation efficiency, which was demonstrated in three diverse laboratory strains of cyanobacteria. We then used an improved RSF1010-based plasmid in mating experiments with cultured samples of wild cyanobacteria. This plasmid, which confers antibiotic resistance and carries a yfp reporter gene, allowed selection of exconjugant cyanobacteria and facilitated the isolation of genetically tractable strains from mixed wild cultures. Improved RSF1010 vectors can be used for bioprospecting genetically tractable strains and are compatible with the CYANO-VECTOR cloning system, a versatile toolbox for constructing plasmids for cyanobacterial genetic engineering.